The Next Generation Fornax Survey (NGFS): V. discovery of a dwarf-dwarf galaxy pair at z = 0.30 and its characterization using deep VLT/MUSE observations - Johnston, Evelyn J.; Ordenes Briceño, Yasna; Grebel, Eva K. (The astrophysical journal, 2019)
We report the detection of a pair of dwarf galaxies at z = 0.30 that may be in the early stages of an interaction. Both galaxies have stellar masses of <109 M ⊙ and display a projected separation of ∼29 kpc and a physical separation of ∼240 kpc. Evidence of ongoing star formation has been found in both galaxies, with neither one showing an enhanced star formation rate that would be expected if they were already interacting. One galaxy displays a disturbed morphology but shows ordered gas rotation, which may reflect a previous minor merger event in the recent history of that system. The nearest spectroscopically confirmed neighbor lies at a distance of 38 Mpc. These results indicate that these dwarf galaxies have no neighboring massive galaxies; however, with the data available we have been unable to determine whether these galaxies are isolated in the field or belong to a group of low-mass galaxies. As a detection of a rare dwarf-dwarf pair beyond the local universe, this system provides an uncommon opportunity to explore the properties of galaxy groups in the low-galaxy mass regime as a function of redshift.
Gesehen am 31.05.2019